Словосполучення як засіб вираження постсегментного компонента називного роз’яснювально-пояснювального змісту - Бакун, Ольга; Bakun, Olha (Східноєвропейський національний університет, 2013)
У статті розглянуто синтаксичні засоби вираження постсегментного компонента одного з різновидів сегментних конструкцій – називного роз’яснювально-пояснювального змісту. Виокремлено структурно-семантичні типи словосполучень у функції постсегментного компонента досліджуваних структур. Syntactical means of postsegmental component expression of one of the types of segmental constructions – nominative of elucidatory-explanatory matter – have been studied in the article. Structural and semantic types of word combinations in the function of a postsegmental component of studied structures have been distinguished.
Word Combination as a Means of Postsegmental Component Expression of a Nominative of Elucidatory-explanatory Matter
Keywords: сегментна конструкція; називний роз’яснювально-пояснювального змісту; постсегментний компонент; словосполучення; структурна класифікація; семантична класифікація; a segmental construction; nominative of elucidatory-explanatory matter; a postsegmental component; a word combination; a structural classification; a semantic classification